Variable stability of a selectable provirus after retroviral vector gene transfer into human cells. - Jolly, D J (1986)
Human lymphoblasts deficient in the enzyme hypoxanthine-guanine phosphoribosyltransferase (HPRT) were infected with an amphotropic helper-free retroviral vector expressing human HPRT cDNA. The stability and expression of the HPRT provirus in five cell lines with different proviral integration sites were examined by determining HPRT mutation and reversion frequencies and by blot hybridization studies. Mutation to the HPRT-negative phenotype occurred at frequencies of approximately 4 X 10(-5) to 3 X 10(-6) per generation. Most mutations in each of the five cell lines were associated with partial or complete deletions or rearrangements of the provirus. Several mutants retained a grossly intact HPRT provirus, and in one such mutant HPRT shutdown resulted from a revertible epigenetic mechanism that was not associated with global changes in proviral methylation. Therefore, mutation and shutdown of the HPRT provirus in human lymphoblasts result from mechanisms similar to those reported for several other avian and mammalian replication-competent retroviruses.